Combining electrochemically reduced graphene oxide and Layer-by-Layer films of magnetite nanoparticles for carbofuran detection - Miyazaki, Celina M.; Adriano, Angela M.; Rubira, Rafael J. G. [UNESP]; Constantino, Carlos J. L. [UNESP]; Ferreira, Marystela (Elsevier B.V., 2020)
Carbofuran (CBF) is a pesticide currently prohibited in many countries. It can cause serious damages in the nervous system and has been associated with cancer. However, CBF residues are still found in food samples around the world. Here, we develop an electrochemical non-enzymatic sensor for rapid and low-cost detection of CBF. Commercial indium fin oxide (ITO) electrodes were modified with a two-step Layer-by-Layer (LbL) approach: i) an LbL film of poly(diallyldimethyl ammonium) (PDDA) and graphene oxide (GO), which is further electrochemically reduced to produce (PDDA/ERGO)-modified ITO electrodes; and ii) an LbL film of magnetite nanoparticles (MNP) and poly(styrene sulfonate) (PSS) to form the ITO/(PDDA/ERGO)(5)/(MNP/PSS)(5), with 5 representing the number of bilayers. The growth mechanism and morphology of the modified electrode were characterized by combining microscopy and optical spectroscopy. The ITO/(PDD/ERGO)(5)/(MNP/PSS)(5) was applied in the electrochemical detection of CBF by differential pulse voltammetry (DPV) in standard solutions, reaching a sensitivity of 0.2543 (mu A cm(-2)) (mu mol L-1) and LOD of 0.407 mu mol L-1, and then in real samples of tap water and soil.
Keywords: Layer-By-Layer film; Carbofuran; Electrochemical sensor; Magnetite; Reduced-Graphene oxide